1986
DOI: 10.1037/0021-843x.95.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Drinking your troubles away: The role of activity in mediating alcohol's reduction of psychological stress.

Abstract: We would like to thank Dome Wilson, Maria Harris, James Dykes, and Diane Sutherland for their valuable assistance on various aspects of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 27 publications
6
52
1
Order By: Relevance
“…What we can say, however, is that our results are generally consistent with Sayette's Appraisal Disruption model (1993) and Hull's Self-Awareness model (1982) but inconsistent with Steele's AttentionAllocation model (Steele et al, 1986). Recall that the latter model predicts that anxiety will increase when drinking takes place during engagement in an aversive activity, while our study found that anxiety decreased when participants drank during engagement in a stressful public speaking task.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…What we can say, however, is that our results are generally consistent with Sayette's Appraisal Disruption model (1993) and Hull's Self-Awareness model (1982) but inconsistent with Steele's AttentionAllocation model (Steele et al, 1986). Recall that the latter model predicts that anxiety will increase when drinking takes place during engagement in an aversive activity, while our study found that anxiety decreased when participants drank during engagement in a stressful public speaking task.…”
Section: Discussioncontrasting
confidence: 42%
“…For example, Steele's AttentionAllocation model (Steele, Southwick, & Pagano, 1986) posits: (1) that alcohol impairs cognition and reduces attentional capacity and (2) that focusing one's limited attentional capacity on a positive or neutral distracter should reduce stress, while focusing on a negative activity should increase stress. Sayette's Appraisal Disruption model (1993) argues that alcohol reduces anxiety by inhibiting the activation of anxiety-related memory networks associated with specific stressors.…”
Section: Cognitive Mechanisms Underlying the Effect Of Alcohol On Socmentioning
confidence: 99%
“…However, the minimization factor differs in an important way from a more traditional avoidance dimension; the minimization factor is a blend of some avoidance coping with positive cognitive restructuring. Rather than avoidance, this state factor could be conceptualized as accommodative coping or secondary control with an emphasis on attention redeployment (Skinner and Wellborn, 1994; see also Steele et al [1986], attention-allocation model). That this factor was associated with more alcohol use is consistent with the self-awareness model (Hull, 1981), which suggests that some individuals regulate alcohol consumption as a distraction in times of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it may directly reduce physiological or psychological tension, or secondly, it may reduce a focusing on the self, and therefore on the stressful thoughts which evoke feelings of tension. Steele et al (1986) proposed a third: alcohol reduces stress because it impairs perception and cognition in a general sense. In relation to the second hypothesis there may be individual variation related to dispositional differences (Wilson, 1988).…”
Section: Moderate Alcohol and Stressmentioning
confidence: 99%